Southeast Asia as One of World’s Primary Sources of Biotic Recolonization Following Anthropocene Extinctions - Procheş, Şerban; Ramdhani, Syd; Hughes, Alice C.; Koh, Lian Pin (Frontiers in Ecology and Evolution, 2021)
The plight of Southeast Asia's animals, plants and ecosystems in the face of unsustainable exploitation and habitat destruction has been illustrated in several recent studies, despite often falling outside global discourse on global conservation priorities. Here we collate biogeographic and phylogenetic information to argue that in fact this beleaguered region is the world's best chance of regaining its natural biodiversity distribution patterns after the current Anthropocene upheaval. The region uniquely combines top diversity values in (a) ancient lineage diversity and (b) cosmopolitan lineage diversity, suggesting that it has acted in the past as a biodiversity museum and source of global colonisation. This is at least partly due to the interplay between latitudinal diversity gradients and continental connectivity patterns. However, the peak values in South China/North Indochina for cosmopolitan tetrapods and their sister lineages suggest that a key feature is also the availability of diverse climatic conditions. In particular, the north-south orientation of the mountain ranges here has allowed for rapid recolonization within the region following past climatic changes, resulting in high survival values and overall exceptional relict lineage diversity. From this starting point, global colonisation occurred on multiple occasions. It is hoped that, with urgent action, the region can once again fulfil this function.